Prevention of falls in the elderly in the home: promoting active ageing - Gemito, Maria (2015)
Objective: To determine the frequency of falls and identify risk factors in the homes of the elderly under the Home Care Service of a village in Alentejo (Portugal). Method: Exploratory, descriptive study. The target group were elderly persons under the Home Care Service (23). The questionnaire consists of open and closed questions, and was based on the Jefferson Area Board for Aging Safety in the Home Assessment; Instrument to Assess the Risk of Falls and Adaptations to Prevent Falls at Home. Results: Of the 23 seniors, 13 were men; the mean age was 85; 10 widowers; 11 live alone; 12 cannot read or write; 17 have experienced falls, loss of balance being the main cause. They report changes in vision (21), hearing (14) and rheumatic diseases (14); hypertension (19); they use 4 or more drugs on a daily basis (16). Conclusion: The physiological changes associated with ageing may increase the risk of falls. Due to the consequences, it is a priority field in community intervention.